The benefit of the vitamin D intake in terms of sarcopenia of senior citizens in Japan during the COVID-19 pandemic - Naomi Nakayama (World Nutrition Journal, 2020)
I would like to be focused on not only protein and vitamin D intake but several nutrients which is considered to be important for health of the elderly in this difficult social condition.